Family Ecology and Way of Life as a Factor Shaping the State of Health of School Children - Naimova Zainab Sattorovna (Global Scientific Publishing, 2023)
The basis for maintaining and strengthening the health of a person and the population as a whole is a healthy lifestyle and the use of methods and means of personal hygiene. A healthy lifestyle of the population is such a way of life that provides a combination of full-fledged biological and social adaptation of each person with the possibility of maximum self-expression of the people, nation, class, social group in specific living conditions and which predetermines and ensures the subsequent development of society. Methods and means of a healthy lifestyle include a whole range of subjective and objective conditions and factors on which the health of an individual and society as a whole depends.
Keywords: Health; healthy lifestyle; family ecology